ANALISIS KEBUTUHAN FUNGSIONAL SISTEM INFORMASI MANAJEMEN KINERJA INTERNAL PERGURUAN TINGGI DI STIKI MALANG - Prasetyo, Koko Wahyu (DINAMIKA DOTCOM, 2018)
A good implementation of information technology within a higher education institution can drive the quality of information availability, business functions integration, and thus the overall performance of the organization. When the information technology is managed unproperly, then it will present enormous challenges for the organization to fulfill its needs of valid information. Those invalid information and false indicators will lead to difficulties in measuring the actual performance of the organization. STIKI Malang is a private college institution located in the city of Malang, Indonesia. Its quality assurance department (Unit Penjaminan Mutu) often find difficulties in taking any required decisions in order to measure the performance of the organization. Some of the processes are considered as inefficient since they are not able to display the needed indicators within the scheduled time. This research analyzes the existing business processes that are related with performance management of the organization. It presents a set of information systems functional requirements model that is resulted from requirements engineering methods. The resulted requirements can be adopted to develop similar performance management systems in higher education environment. Keywords: key performance indicator, performance management, quality assurance, information systems, functional requirements, higher education